Pengembangan Media Pembelajaran Mufrodat Bahasa Arab Berbasis Android di MIN 3 Bantul Yogyakarta - Tolibuddin Siregar; Aulia Azmi Alkhairi (Mahira: Journal of Arabic Studies & Teaching, 2024)
This study aims to develop Android-based Arabic mufrodat learning media that is feasible and effective for grade 3 students at MIN 3 Bantul Yogyakarta. The method used is Research and Development (R&D) with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The results of the analysis showed the need for interactive and contextual learning media to overcome students' difficulties in reading Arabic letters and memorizing vocabulary. The media product was developed in the form of an Android application called Al-Araby, validated by media experts, material experts, and teachers, with validation results of 71%, 81%, and 4.8 on a scale of 5, respectively, indicating a high level of feasibility. The effectiveness of the media was tested through pre-test and post-test on 48 students, with an increase in the average score from 81.4 to 96.6. The paired sample t-test results showed a significance of 0.01 <0.05, signifying a statistically significant increase. Learners' responses also showed enthusiasm and increased interest in learning. Thus, this learning media is proven to be valid, feasible, and effective to use in learning Arabic at the elementary level.